A Comparison of the Antimicrobial Resistance Patterns of Gram-Positive Cocci Isolated from Community-Private and University-Affiliated Hospitals from Puerto Rico - Vázquez, Guillermo J.; Robledo, Iraida E.; Arroyo, Angel; Nadal, Eduardo; Rodríguez, Radamés; Bermúdez, Myriam; Colón, Miguel (Puerto Rico Health Sciences Journal, 2011)
see manuscript